Extension of the phenotype of biallelic loss‐of‐function mutations in SLC25A46 to the severe form of pontocerebellar hypoplasia type I. Issue 2 (8th November 2017) - Braunisch, M.C.; Gallwitz, H.; Abicht, A.; Diebold, I.; Holinski‐Feder, E.; Van Maldergem, L.; Lammens, M.; Kovács‐Nagy, R.; Alhaddad, B.; Strom, T.M.; Meitinger, T.; Senderek, J.; et al.
Abstract : Biallelic mutations in SLC25A46, encoding a modified solute transporter involved in mitochondrial dynamics, have been identified in a wide range of conditions such as hereditary motor and sensory neuropathy with optic atrophy type VIB (OMIM: *610826) and congenital lethal pontocerebellar hypoplasia (PCH). To date, 18 patients from 13 families have been reported, presenting with the key clinical features of optic atrophy, peripheral neuropathy, and cerebellar atrophy. The course of the disease was highly variable ranging from severe muscular hypotonia at birth and early death to first manifestations in late childhood and survival into the fifties. Here we report on 4 patients from 2 families diagnosed with PCH who died within the first month of life from respiratory insufficiency. Patients from 1 family had pathoanatomically proven spinal motor neuron degeneration (PCH1). Using exome sequencing, we identified biallelic disease‐segregating loss‐of‐function mutations in SLC25A46 in both families. Our study adds to the definition of the SLC25A46‐associated phenotypic spectrum that includes neonatal fatalities due to PCH as the severe extreme. Abstract :